2019
DOI: 10.1029/2019gb006200
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Arctic Ocean Response to Doubling of Riverine Carbon and Nutrient Delivery

Abstract: The Arctic Ocean, more than any other ocean, is influenced by riverine input of carbon and nutrients. That riverine delivery is likely to change with climate change as runoff increases, permafrost thaws, and tree lines advance. But it is unknown to what extent these changes in riverine delivery will affect Arctic Ocean primary production, air‐to‐sea CO2 fluxes, and acidification. To test their sensitivity to changing riverine delivery, we made sensitivity tests using an ocean circulation model coupled to an oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 111 publications
(173 reference statements)
0
51
1
Order By: Relevance
“…Organic carbon inputs from permafrost thaw (coastal erosion, river inputs) and glacier and ice sheet melt have been the topic of much attention recently, due to the potential for these vast, labile carbon stores to be exported to the coastal ocean (Hood et al, 2015;McClelland et al, 2016;Le Fouest et al, 2018;Wadham et al, 2019). Carbon in river runoff, eroded permafrost sediments, and glaciers has been found to be highly labile to microbial communities ( Table 2; Vonk et al, 2013;Paulsen et al, 2017;Sipler et al, 2017), causing both the quantity and quality of these inputs to influence ecosystem carbon cycling, and potentially converting large areas of coastal ocean into sources, rather than sinks, of CO 2 (discussed further below; Terhaar et al, 2019). However, as with inorganic nutrients, glacial and ice sheet organic carbon concentrations are orders of magnitude lower than runoff from the large Arctic Rivers and coastal erosion (Hood et al, 2015;Paulsen et al, 2017;Hopwood et al, 2018;Wadham et al, 2019).…”
Section: Regionality and Seasonality Of Freshwater Dictates The Accesmentioning
confidence: 99%
“…Organic carbon inputs from permafrost thaw (coastal erosion, river inputs) and glacier and ice sheet melt have been the topic of much attention recently, due to the potential for these vast, labile carbon stores to be exported to the coastal ocean (Hood et al, 2015;McClelland et al, 2016;Le Fouest et al, 2018;Wadham et al, 2019). Carbon in river runoff, eroded permafrost sediments, and glaciers has been found to be highly labile to microbial communities ( Table 2; Vonk et al, 2013;Paulsen et al, 2017;Sipler et al, 2017), causing both the quantity and quality of these inputs to influence ecosystem carbon cycling, and potentially converting large areas of coastal ocean into sources, rather than sinks, of CO 2 (discussed further below; Terhaar et al, 2019). However, as with inorganic nutrients, glacial and ice sheet organic carbon concentrations are orders of magnitude lower than runoff from the large Arctic Rivers and coastal erosion (Hood et al, 2015;Paulsen et al, 2017;Hopwood et al, 2018;Wadham et al, 2019).…”
Section: Regionality and Seasonality Of Freshwater Dictates The Accesmentioning
confidence: 99%
“…May the changing sea ice conditions and/or increasing levels of particulate/aggregate matter due to elevated pelagic and sympagic primary production provide such low-oxygen loci and stimulate heterotrophic BNF? B: Freshwater input from rivers, permafrost thaw, and glaciers is increasing in the AO (Mouginot et al, 2019;Terhaar et al, 2019) and may affect levels of trace metals (e.g., iron and molybdenum), DOM and particulate organic matter (POM) (Holmes et al, 2012;Hopwood et al, 2020;Michaud et al, 2020). To what extent may trace metals supplied by glacial melt and river runoff stimulate BNF?…”
Section: Cyanobacterial Diazotrophs May Be Of Higher Relative Abundanmentioning
confidence: 99%
“…Therefore, with climate change proceeding at elevated speed in the Arctic region (Serreze et al, 2009;AMAP, 2019;Meredith et al, 2019), it is of importance for global carbon cycling to understand and predict current and future net primary production in the AO. Ongoing and predicted drastic changes in the AO include, e.g., decreasing area, thickness and age of sea ice (Stroeve and Notz, 2018), altered water column stratification (Peralta-Ferriz and Woodgate, 2015;Polyakov et al, 2020), rapid ocean acidification (Terhaar et al, 2020), increasing surface temperatures (Fyfe et al, 2013;Timmermans et al, 2017), rising discharge of freshwater (Terhaar et al, 2019), intensifying thaw of permafrost (Biskaborn et al, 2019), and large-scale hydrographical changes (e.g., Bluhm et al, 2015;Proshutinsky et al, 2015;Woodgate, 2018). The continuous thinning and withdrawal of sea ice stimulate pelagic and sympagic (sea ice-associated) primary production, but with nutrient availability -in particular nitrogen (N) -as a key determinant (Tremblay and Gagnon, 2009;Vancoppenolle et al, 2013;Arrigo and van Dijken, 2015;Fernández-Méndez et al, 2015;Lewis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between these models, as well as observed changes in NPP 6 , 7 , 11 have mainly been related to the specific physical conditions of the Arctic Ocean, such as sea-ice extent and ocean circulation. However, recent studies have suggested that terrigenous nutrient inputs from rivers and coastal erosion might be another key control of Arctic Ocean NPP 12 14 , a process that has often been neglected in observational studies 6 , 7 , 11 and models 8 , 10 .…”
Section: Introductionmentioning
confidence: 99%